The Risk of Gold Price Fluctuations on the Balance of Assets and Liabilities: An Analysis within the Framework of Asset-Liability Management at the XYZ Church Welfare Fund - Krisna Yoga Pradigdya (Eduvest - Journal of Universal Studies, 2026)
The XYZ Church Welfare Fund (BAKES) manages benefit obligations denominated in gold grams, creating structural exposure to gold price volatility. However, its investment portfolio remains dominated by deposits with fixed returns, lacking assets that move in tandem with gold prices, thereby generating an Asset-Liability mismatch. This research aims to analyze risk fluctuations price gold to balance assets and liabilities in Management of the XYZ Church's BAKES welfare fund. Obligations benefit participant set in gram of gold so that its value very influenced by dynamics price gold in the market. Meanwhile that, portfolio asset BAKES investment is still dominated by deposit instruments with characteristics reward results still that doesn't own sensitivity mark one way with change price gold. This research used approach descriptive analytical with method studies case through secondary data analysis in the form of document policy management wealth, report portfolio investment, participant data, and price data gold 2022-2025 period. Research results This show that nominally condition​ BAKES solvency is still be in position safe Because mark asset bigger than obligations. However, the structure portfolio investments that have not been implement investment gold cause exposure risk to fluctuations price gold and potential cause imbalance between assets and liabilities in long term. Therefore that, is necessary strengthening management strategies asset in Asset Liability Management framework, including utilization investment gold as a protection instrument value, use guard stability finance and sustainability fulfillment welfare fund obligations.